Macropinocytosis regulates cytokine expression through Erk signaling in LPS-stimulated macrophages - Li Wang; Yanan Li; Yuxin He; Yuchen Fang; Hitomi Mimuro; Adam C. Midgley; Sei Yoshida (Cell Structure and Function)
Macropinocytosis, a type of large-scale endocytosis process, is induced in macrophages by extracellular stimuli, including lipopolysaccharide (LPS). In addition to uptake function, emerging evidence supports a link between macropinocytosis and LPS-induced signal transduction. Following LPS stimulation, membrane ruffles are induced to form cup-like structures known as macropinocytic cups, a necessary precursory step for macropinocytosis. We have recently shown that Akt is activated at the cups and is an upstream regulator of the Iκ-B/NF-κB pathway implicated in the production of IL-1α and IL-6. Here, we further investigated the molecular mechanisms and show that the macropinocytic cups also regulated the Ras/Mek/Erk/c-Fos pathway to modulate IL-1β expression independently of the Akt pathway. In addition, we observed that the cup-dependent Akt pathway downregulated the expression of IL-10, in which the activation of the Erk pathway was critical. Taken together, we propose that macropinocytic cups separately modulate the Akt and Erk pathways in cytokine expression. Key words: macropinocytosis, Erk, IL-1β, IL-10